ANALISIS FAKTOR YANG MEMPENGARUHI PROFITABILITAS - Fauzan, Ahmad Fikri Taftazani; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study was to analyze the effect of independent variables of capital structure, liquidity, institutional ownership, and growth on profitability. The sample in this study was selected using purposive sampling method so that as many as 69 companies from 150 manufacturing companies listed on the IDX were used as research objects. This study uses secondary data which is processed using panel data regression analysis and application Eviews version 12. Based on the analysis, it is found that capital structure, liquidity, institutional ownership, and growth simultaneously have a significant effect on profitability. The results of this study indicate that growth have a positive and significant effect on profitability, and capital structure, liquidity, and institutional ownership has a negative and significant effect profitability. The implication in this research is the need for careful investors to read more in the financial statements related to company liquidity and the need for a good composition of institutional ownership in a company.